PERAN PENDIDIKAN AGAMA ISLAM DALAM PENANAMAN NILAI-NILAI KELUARGA SAKINAH SEBAGAI UPAYA PENCEGAHAN PERCERAIAN DI KECAMATAN TEGALOMBO KABUPATEN PACITAN - Ismail (DEVELOPMENT: Journal of Community Engagement, 2026)
This study aims to analyze the strategic role of Islamic Religious Education (Pendidikan Agama Islam/PAI) in instilling keluarga sakinah values as a preventive approach to divorce in Tegalombo District, Pacitan Regency. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving married couples, religious leaders, and Islamic counselors. Data analysis was conducted using data reduction, data display, and conclusion drawing. The findings indicate that PAI plays a significant role in strengthening family resilience by internalizing values such as patience, responsibility, mutual respect, communication, and deliberation in marital life. However, the implementation of these values remains suboptimal, as religious education is still predominantly focused on ritual aspects rather than practical relational skills, including conflict management and emotional regulation. Economic pressures, lifestyle changes, and the influence of digital media further complicate the application of keluarga sakinah values in everyday family life. The study also finds that religious leaders and Islamic counselors contribute positively to conflict resolution, although their roles tend to be reactive and not yet integrated into sustainable family development programs. This study concludes that strengthening PAI as a preventive strategy requires a more systematic, contextual, and integrative approach involving families, religious institutions, and local communities.